Pengelolaan Badan Usaha Milik Negara Sebelum Undang-Undang Nomor 1 Tahun 2025 - Retno Kus Setyowati (Jurnal Penelitian Hukum De Jure, 2026)
SOEs, in addition to being regulated in Law No. 40/2007 concerning Limited Liability Companies, are also regulated by Law No. 19/2003 concerning SOEs and Law No. 17/2003 on State Finance, which carries consequences that if SOEs lose their jobs, they will be subject to criminal liability, namely corruption. The issuance of Law No. 1/2025 concerning the third amendment to Law No. 19 of 2003 brought about a change in the responsibility of directors of SOEs that suffered losses. Prior to Law No. 1/2025, the Business Judgement Rule was not considered in Court decisions, and losses by state-owned companies were a criminal act of corruption. In the case of Karen Agustiawan as President Director of PT Pertamina (Persero) and President Commissioner of PT Pertamina Hulu for the action of BMG Block Participating Interest Australia, the Cassation Decision applied the Business Judgement Rule, but in the second case, the Panel of Cassation Judges did not apply it, so it was sentenced. Under Law No. 1/2025, SOEs' losses are treated as business risks rather than as state losses that can be punished. The method used is normative law research with various approaches, namely positive law and its changes.